1999
DOI: 10.1002/(sici)1097-4636(199901)44:1<1::aid-jbm1>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of cultured human bone cells to novel polymers

Abstract: The initial attachment of human bone-derived cells (HBDC) to several polymer systems has been studied in vitro. A novel polymer system based on poly(ethyl methacrylate) polymer and tetrahydrofurfuryl methacrylate monomer (PEMA/THFMA) was compared with a variant in which THFMA was replaced by 2-hydroxyethyl methacrylate (PEMA/HEMA). Tissue culture polystyrene (TCPS) and polystyrene (PS) were used as reference materials. The ability of the substrates to adsorb the attachment glycoproteins fibronectin (Fn) and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…Rezania and Healy (1999) showed that the response of cells on RGD-grafted surfaces is dependent on the specific peptide sequence. RGD peptides enhance the rate of cell spreading and adhesion strength (McFarland et al, 1999;Rezania et al, 1997). Cell binding to covalently linked RGD peptides causes increase in expression of integrins and FA molecules and promotes resistance to apoptotic stimuli (Cavalcanti-Adam et al, 2002;Grigoriou et al, 2005).…”
Section: Surface-bound Adhesive Peptides Direct Cellular Adhesion Viamentioning
confidence: 99%
“…Rezania and Healy (1999) showed that the response of cells on RGD-grafted surfaces is dependent on the specific peptide sequence. RGD peptides enhance the rate of cell spreading and adhesion strength (McFarland et al, 1999;Rezania et al, 1997). Cell binding to covalently linked RGD peptides causes increase in expression of integrins and FA molecules and promotes resistance to apoptotic stimuli (Cavalcanti-Adam et al, 2002;Grigoriou et al, 2005).…”
Section: Surface-bound Adhesive Peptides Direct Cellular Adhesion Viamentioning
confidence: 99%
“…20 Among those, fibronectin, a 550-kDa extracellular matrix glycoprotein, is well known to increase cell adhesion on abiotic surfaces. 18,21 Fibronectin would also be involved in the early stages of osteogenesis [22][23][24] and in mineralization processes 25,26 The present work focuses on optimizing cell adhesion onto calcium-phosphate ceramics with the use of a fibronectin interface. Preliminary studies performed in the laboratory indicated that a labile layer on hydroxyapatite materials gives rise to fibronectin precipitation and prevents its adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)(4) Alteration in any of these physical characteristics can profoundly influence short-term activities (adhesion) and long-term functional events (gene expression and protein synthesis). (5)(6)(7)(8)(9)(10)(11)(12) How bone cell-material interaction mediates complex functions such as those linked to the synthesis of the extracellular matrix (ECM) and the osseointegration process remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…One motif that is present in a number of matrix proteins is the arginine-glycine-aspartic acid (RGD) sequence. (13) RGD is an integrin-binding motif that enhances osteoblast attachment and spreading, (8,14) induces mineralization of the ECM, and influences downstream maturation events. (7) Im-mobilization of RGD peptides on titanium implants by physiosorption has been reported to significantly increase bone formation, (15,16) although free RGD-containing peptides induce skeletal cell death.…”
Section: Introductionmentioning
confidence: 99%